Results of complex treatment of patients with locally advanced squamous cell carcinoma of the paranasal sinuses and nasal cavity using induction chemotherapy - T. I. Dеshkina; L. V. Bolotina; A. R. Gevorkov; A. V. Boyko; A. L. Kornietskaya; A. P. Polyakov; P. V. Golubev; R. S. Sydykova; A. A. Fedenko (Опухоли головы и шеи)
Introduction. About 600 new cases of malignant neoplasms of the paranasal sinuses and nasal cavity are detected annually in Russia. To date, there are no randomized trials to determine the optimal treatment algorithm for this group of patients. Data on the use of induction chemotherapy in squamous cell carcinoma of sino-nasal tract are limited to a small series of clinical observations and, often, are retrospective in nature.Aim. Evaluation of the effectiveness of induction chemotherapy in patients with locally advanced squamous cell carcinoma of the paranasal sinuses and nasal cavity.Materials and methods. Since 2012, 22 patients with locally advanced cancer of the paranasal sinuses and nasal cavity have been treated in our center, who underwent 3-component induction chemotherapy according to the TPF protocol. Evaluation of the effectiveness of treatment was carried out according to the criteria of Response evaluation criteria in solid tumors 1.1 (RECIST 1.1). Patients with a decrease in the tumor size by 30 % or more, were followed by radiation therapy in doses of 66–70 Gy. Patients with a residual tumor underwent surgery after the end of chemoradiotherapy.Results. In 21 patients available for analysis, overall response rate after induction chemotherapy was 71 %: complete response was registered in 3 (14 %) patients, partial response in 12 (57 %), stable disease in 4 (19 %). Progression disease after 3 courses of induction chemotherapy was detected in 2 (10 %) patients.Conclusions. Thus, induction chemotherapy in patients with squamous cell carcinoma of sino-nasal tractseems to be a promising direction for investigation, that can significantly improve the long-term results of treatment of this category of patients and help to avoid of disabling surgery in some of them.